Revisiting Secularism in Western Christendom: A Theological and Sociological Approach - Kevin Nobel Kurniawan (Societas Dei: Jurnal Agama dan Masyarakat, 2020)
The objective of this article is to revisit the process of secularization in the decline of Christian religion in the West through a theological and societal discussion on a theoretical level. By arguing a societal perspective alone is insufficient to provides a specific explanation to religious decline, a theological perspective would provides a prior explanation to further clarify how the process of secularization operates in relation to the internal dynamic of the Christian religion. The expositions of such arguments would argue that the process of secularization can be differentiates into several parts: The objectivation of Christian beliefs for capitalism in European industrialization, the de-attachment of individual to spiritual faith, and the process of individualization and consumerism that deconstructs religion in postmodernity. This article will posit the theological Kierkegaardian view of Christendom in dialogue with sociological arguments on modernity and postmodernity, and also to relate such findings into the Indonesian context to provides conceptual anticipation for postmodern social changes.KEYWORDS: secularism, christendom, Kierkegaard, modernity, liquid modernity, community.